The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1365-2702.2007.01795.x
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming health inequalities by using the Bug Busting ‘whole‐school approach’ to eradicate head lice

Abstract: Incorporation of the Bug Busting approach to head lice into clinical practice in school communities contributes to sustainable control whilst overcoming health inequalities in participating families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 31 publications
0
22
1
1
Order By: Relevance
“…Much professional time spent previously with the large number of worried parents could now be saved, and adequate time given to the few families who were dependent on one-to-one guidance. 51,52 D DI IS SC CU US SS SI IO ON N The 1970-1973 Teesside experience 10,12,30 revealed that co-ordinated detection compensated for poorly performing treatments in an anti-head louse campaign. Families became aware that they could not rely on medication to kill louse eggs and intensified egg removal with a Derbac comb.…”
Section: -2008mentioning
confidence: 98%
“…Much professional time spent previously with the large number of worried parents could now be saved, and adequate time given to the few families who were dependent on one-to-one guidance. 51,52 D DI IS SC CU US SS SI IO ON N The 1970-1973 Teesside experience 10,12,30 revealed that co-ordinated detection compensated for poorly performing treatments in an anti-head louse campaign. Families became aware that they could not rely on medication to kill louse eggs and intensified egg removal with a Derbac comb.…”
Section: -2008mentioning
confidence: 98%
“…Relying on products alone to contain head louse infestations at a reasonable level will not be sufficient. Public health programs at local community level involving parents, schools, and community services with accurate screening methods (Combescot 1990;Demaeseneer et al 2000;Mumcuoglu et al 2007;Jahnke 2009) and synchronized treatment campaigns with effective treatments will be needed (Meinking et al 1986;Combescot 1990;Ibarra et al 2007;Feldmeier 2012).…”
Section: Recommendations For Practicementioning
confidence: 99%
“…At the time of the study the most widely promoted combing method was “Bug-Busting” (Community Hygiene Concern, London), which used a fine toothed plastic comb for wet combing with conditioner, repeated at 3–4 day intervals for 2 weeks. It suggested the first combing could remove all lice so only newly hatched nymphs would be found during subsequent combing sessions before they could mature and lay eggs 5 . Before our investigation only two studies of wet-combing had been conducted.…”
Section: Introductionmentioning
confidence: 99%